Study on hierarchies and networks in health policy for elderly people in Mexico - Linares Bravo, Bárbara Carolina; Nazar Beutelspacher, Austreberta; Sánchez Ramírez, Georgina; Zapata Martelo, Emma; Salvatierra Izaba, Benito (Población y Salud en Mesoamérica, 2017)
The non-maternity in Mexico is emerging as a complex phenomenon different from the highly urbanized and industrialized societies in which primarily has been studied. The unequal conditions in which it takes place refer to a variety of experiences that need to be documented. This study seeks to contribute to the knowledge of non-maternity in Mexico, exploring, from secondary sources and descriptive analysis, its most important social and economic aspects. The results confirm that non-maternity occurs under different socioeconomic contexts, that become even antagonistic. Non-marital union was presented as an important aspect of non-maternity that, not having been associated with migration rates, shows that in Mexico women who are not mothers neither are wives, thereby suggesting a double transgression of the hegemonic model of womanhood, while it is revealing a reality hitherto little visible of women who are neither mothers nor wives: the women with physical limitations to work.